2014
DOI: 10.1590/s0100-83582014000300009
|View full text |Cite
|
Sign up to set email alerts
|

Interação competitiva de genótipos de arroz e papuã

Abstract: RESUMO -Objetivou-se com este trabalho avaliar a resposta competitiva de genótipos de arroz na presença de um biótipo de papuã (Brachiaria plantaginea), em diferentes proporções de plantas na associação. O delineamento experimental adotado foi o completamente casualizado com quatro repetições. Os tratamentos foram arranjados em série de substituição e constituíram-se de cinco proporções de plantas de arroz e do papuã na associação (100:0, 75:25, 50:50, 25:75 e 0:100). Aos 50 dias após a emergência das espécies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
1
9
0
2
Order By: Relevance
“…There are several methods to investigate the competitive relationships between plants; among them, the experiments in replacement series stand out, which have been widely used for studies of different crop/weeds (Aminpanah and Javadi 2011;Bianchi et al 2006;Galon et al 2014;Rigoli et al 2008;Wandscheer and Rizzardi 2013). This method allows the understanding of the competitive process between plants, especially when related to the effect of the population as well as of the crop and weeds proportion (Aminpanah and Javadi 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several methods to investigate the competitive relationships between plants; among them, the experiments in replacement series stand out, which have been widely used for studies of different crop/weeds (Aminpanah and Javadi 2011;Bianchi et al 2006;Galon et al 2014;Rigoli et al 2008;Wandscheer and Rizzardi 2013). This method allows the understanding of the competitive process between plants, especially when related to the effect of the population as well as of the crop and weeds proportion (Aminpanah and Javadi 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in substitutive series have found that usually crops have higher competitive ability than weeds (Agostinetto et al 2013;Galon et al 2014;Moraes et al 2009). This behavior is explained by the fact that the negative effect of weeds is not restricted by the largest individual competitive ability, but mainly due to the level of infestation in the area (Vilà et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This is a probable indicator that the competitive ability of these species may be centered on Density, one of the most notable phytosociological parameters in plant community dynamics (Concenço, Andres, Teló, Martins, & Moisinho, 2017). Alexandergrass, on the other side, seems to center its competitive ability most probably on dominance (Galon et al, 2014) since its dry mass per area was high from low plant densities onwards.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms of stomatal opening and closure depend on factors such as solar radiation, CO 2 level in the mesophyll, relative air humidity, water potential, wind speed and growth substances inherent to each species (Galon et al, 2014), as well as others secondary factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation